Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
OBJECTIVES: Therapeutic drug monitoring (TDM) of gentamicin is critical to ensure efficacy and minimize toxicity. We report a candidate reference measurement procedure (RMP) to quantify gentamicin in biological matrices, establishing an unbroken traceability chain to the International System of Units (SI). METHODS: An isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC-MS/MS) method was validated using quantitative nuclear magnetic resonance (qNMR) spectroscopy to replace historical biological activity-based standardization with gravimetric mass. Strict ID-MS principles were applied to the major congeners (C1, C1a, and C2). Isomers C2a and C2b, eluting at distinct retention times, were quantified using C2-D3 as a structural analog internal standard. Pharmacokinetic-based analytical performance specifications set the maximum allowable standard measurement uncertainty (k=1) at ≤6.7 %. RESULTS: The RMP demonstrated high analytical control, with trueness (bias 1.0-2.8 %) and within-run precision (CV 0.2-0.9 %) fulfilling clinical requirements. Expanded measurement uncertainties (k=2) for target value assignment ranged from 2.0 to 2.4 %. Comparison with the current JCTLM-listed RMP revealed a systematic negative bias of -9.2 %. A three-way method correlation confirmed these differences as a direct result of the metrological transition from activity to SI-traceable mass units. CONCLUSIONS: This candidate RMP provides a robust, highly precise SI-traceable foundation for gentamicin quantification. While the resulting downward shift in reported concentrations may necessitate re-evaluating established clinical decision thresholds and TDM protocols, the clinical requirement for such adjustments remains to be fully determined.